Potential probiotic and functional properties of Brettanomyces strains isolated from kombucha tea - Areal-Hermida, Lara; Coelho, Pedro; Pichardo-Gallardo, Ángeles; Prudêncio, Cristina; Sieiro, Carmen (Frontiers in Microbiology, 2024)
Kombucha, a beverage traditionally obtained through the fermentation of tea, is believed to have beneficial health properties. Therefore, characterizing the microorganisms responsible for this fermentation is essential to demonstrate its potential health benefits and to identify candidates for new probiotics. In this study, four probiotic yeast strains isolated from kombucha tea were identified, by the PCR-RFLP analysis of the ribosomal ITS region and the sequence of the D1/D2 domain of the 26S rDNA, as Brettanomyces bruxellensis (UVI55 and UVI56) and B. anomalus (UVI57 and UVI58). Properties relevant to probiotics were also studied in these strains. All of them showed excellent survival in simulated gastric (99%–100%) and duodenal (95%–100%) juices. The ability to self-aggregate (38%–100%), adhesion to xylene (15%–50%) and, above all, adhesion to Caco-2 cells (4%–21%), revealed its potential capacity to adhere to the intestinal epithelium. In addition, the tested strains showed excellent antioxidant capacity (82%–94%), antimicrobial activity against different pathogens (Escherichia coli, Staphylococcus aureus, Salmonella enterica, Listeria monocytogenes, and Bacillus cereus), as well as remarkable cytotoxic activity against colon, melanoma and ovarian tumor cell lines. Finally, using Caenorhabditis elegans as a model, strain UVI56 exhibited ability to both extend the lifespan of the nematode and protect it against infection by S. enterica. These results support the probiotic and functional properties of the analyzed strains. In conclusion, the study revealed that kombucha tea could be a source of potential probiotics that contribute to its health-promoting properties and that the characterized Brettanomyces strains could be exploited directly as probiotics or for the development of new functional foods.